The Implementation of Government Administration in Gampong Blok Sawah - Ismail (SIASAT, 2020)
The purpose of this study was to determine how the implementation of Gampong government administration and the obstacles experienced in the management of Gampong government administration at Keuchik Gampong Office, Block Sawah, Pidie Regency. The method used is a qualitative approach, data collection through observation, documentation, and interviews. In the data validity checking technique used triangulation with the use of sources. The results of the study found that the apparatus of the management of Gampong government administration was not fully capable of providing services to the community as desired by the community. However, if the obstacles faced in carrying out the management of Gampong government administration are human resource factors and their good management in the process of carrying out implementing administration mechanisms for the community so that it is easier to complete administrative arrangements. From the results of the above study it can be concluded that the implementation of Gampong government administration at Keuchik Gampong office Blok Sawah, Pidie Regency provided by officers in general is in accordance with established procedures, however the community still wants an improvement in the quality of administrative management, so that it is faster and not convoluted.